2022
DOI: 10.1186/s12935-022-02550-w
|View full text |Cite
|
Sign up to set email alerts
|

KRAS acting through ERK signaling stabilizes PD-L1 via inhibiting autophagy pathway in intrahepatic cholangiocarcinoma

Abstract: Background While the correlation between PD-L1 expression and KRAS mutation has been previously reported in other solid tumors such as non-small cell lung cancer (NSCLC), whether PD-L1 can be modulated by ERK signaling downstream of KRAS in intrahepatic cholangiocarcinoma (iCCA) and the underlying molecular regulatory mechanism remain unclear. Methods The expression of ERK, p-ERK, PD-L1 and autophagy markers following KRAS knockdown or Ras/Raf/MEK/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…16,17 It is not revealed much in BTC; however, some studies showed that KRAS mutation induces the expression of PD-L1. 18,19 Our data did not show any correlation between KRAS and PD-L1 in BTC patients; However, as this study only included small number of patients, further studies would be needed.…”
Section: Therapeutic Advances In Gastroenterologymentioning
confidence: 69%
“…16,17 It is not revealed much in BTC; however, some studies showed that KRAS mutation induces the expression of PD-L1. 18,19 Our data did not show any correlation between KRAS and PD-L1 in BTC patients; However, as this study only included small number of patients, further studies would be needed.…”
Section: Therapeutic Advances In Gastroenterologymentioning
confidence: 69%
“…Compared with the data from the above clinical studies of monotherapy, the results of our study demonstrated relatively better therapeutic effects, which may also be related to the low overall ECOG scores of patients. It has also been shown that some targeted drugs can improve the immunotherapy response rate by promoting the activation and recruitment of CD8 + T cells, enhancing the expression of PD-L1, and eliminating immunosuppressive tumor microenvironment (TME), thus suggesting that the combination of targeted therapy and immunotherapy plays a synergistic role, which can be used as a new therapeutic strategy 24,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…A study based on 17,909 CRC patients found that rare KRAS mutation subtypes such as A59T were correlated with predictive immunotherapy response biomarkers [ 134 ]. The inhibition of ERK signaling was found to assist in reducing PD-L1 expression through autophagy in intrahepatic cholangiocarcinoma (iCCA), indicating that ERK-targeted therapy may be combined with anti-PD-(L)1 immunotherapy for KRAS-mutant iCCA [ 135 ]. Equipping cetuximab on the surface of NK cells may solve the problem of cetuximab resistance in KRAS-mutant CRC [ 136 ].…”
Section: Advances In Drug Resistance and Oncological Mechanisms Of Kr...mentioning
confidence: 99%